Integrating laboratory and field studies to assess impacts of discharge from a uranium mine and validate a water quality guideline value for magnesium. (26th October 2018) - Trenfield, Melanie A; Harford, Andrew J; Mooney, Thomas; Ellis, Mark; Humphrey, Chris; van Dam, Rick A
ABSTRACT: Magnesium (Mg) is a primary contaminant in mine water discharges from the Ranger Uranium Mine (north Australia). Site‐specific water quality guideline values (WQGVs) for Mg have been derived from laboratory and field studies. Contaminated groundwater with elevated electrical conductivity and metals (Mg, Mn, U, SO4, and Ca) was detected flowing from the mine site into adjacent surface waters. This provided an opportunity to investigate the protectiveness of the Mg WQGV by conducting an integrated laboratory and field study. A direct toxicity assessment (DTA) of the groundwater was conducted with local tropical freshwater species: duckweed ( Lemna aequinoctialis ), green hydra ( Hydra viridissima ), and the aquatic snail Amerianna cumingi . An in situ toxicity assessment was carried out in the creek receiving diluted groundwater by use of the same species of snail, to aid interpretation of laboratory‐derived data. The toxicity of the contaminated groundwater was higher than Mg‐only toxicity testing for H. viridissima, with other elevated metals and major ions contributing to toxicity. However, for duckweed and snail, the contaminated groundwater was less toxic than the Mg‐only testing. In situ snail monitoring supported laboratory exposures, showing no effect on reproduction of A. cumingi exposed to an average of approximately 5 mg/L Mg; however, a very small effect was noted closer to the groundwater source, probably associated with other contaminants. The minimal toxicity observed for L. aequinoctialis and A. cumingi, despite the elevated Mg, can be explained by the high calcium (Ca) concentration of the water and the potential amelioration of metal toxicity. The extent of Ca amelioration of Mg toxicity was organism dependent. This study affirms the proposed environmental rehabilitation standard of 3 mg/L Mg for surface waters with a Ca concentration typical of water from this mine site. Integr Environ Assess Manag 2019;15:64–76. © 2018 SETAC Key Points: The toxicity of a contaminated groundwater from a uranium mine in north Australia was assessed with a suite of tropical freshwater species. An integrated laboratory and field study was conducted to investigate the protectiveness of the water quality guideline value for 1 of the key potential contaminants of concern, magnesium. Results show that keeping chronic exposure to Mg is kept below 2.5–5 mg/L Mg should protect aquatic ecosystems downstream of the mine. The results support the proposed environmental rehabilitation standard for the mine of 3 mg/L Mg for surface waters of a 3.5:1 Mg:Ca ratio.